Deletion of microRNA-183-96-182 Cluster in Lymphocytes Suppresses Anti-DsDNA Autoantibody Production and IgG Deposition in the Kidneys in C57BL/6-Faslpr/lpr Mice - Wang, Zhuang; Heid, Bettina; Lu, Ran; Sachdeva, Mohit; Edwards, Michael R.; Ren, JingJing; Cecere, Thomas E.; Khan, Deena; Jeboda, Taschua; Kirsch, David G.; Reilly, Christopher M.; Dai, Rujuan; et al. (Frontiers in Genetics, 2022)
Dysregulated miRNAs have been implicated in the pathogenesis of systemic lupus erythematosus (SLE). Our previous study reported a substantial increase in three miRNAs located at the miR-183-96-182 cluster (miR-183C) in several autoimmune lupus-prone mice, including MRL/lpr and C57BL/6-lpr (B6/lpr). This study reports that in vitro inhibition of miR-182 alone or miR-183C by specific antagomirs in activated splenocytes from autoimmune-prone MRL/lpr and control MRL mice significantly reduced lupus-related inflammatory cytokines, interferon-gamma (IFN, and IL-6 production. To further characterize the role of miR-182 and miR-183C cluster in vivo in lupus-like disease and lymphocyte phenotypes, we used hCD2-iCre to generate B6/lpr mice with conditional deletion of miR-182 or miR-183C in CD2+ lymphocytes (miR-182-/-B6/lpr and miR-183C-/-B6/lpr). The miR-182-/-B6/lpr and miR-183C-/-B6/lpr mice had significantly reduced deposition of IgG immunocomplexes in the kidney when compared to their respective littermate controls, although there appeared to be no remarkable changes in renal pathology. Importantly, we observed a significant reduction of serum anti-dsDNA autoantibodies in miR-183C-/-B6/lpr mice after reaching 24 weeks-of age compared to age-matched miR-183Cfl/flB6/lpr controls. In vitro activated splenocytes from miR-182-/-B6/lpr mice and miR-183C-/-B6/lpr mice showed reduced ability to produce lupus-associated IFN. Forkhead box O1(Foxo1), a previously validated miR-183C miRNAs target, was increased in the splenic CD4+ cells of miR-182-/-B6/lpr and miR-183C-/-B6/lpr mice. Furthermore, in vitro inhibition of Foxo1 with siRNA in splenocytes from miR-182-/-B6/lpr and miR-183C-/-B6/lpr mice significantly increased IFN expression following anti-CD3/CD28 stimulation, suggesting that miR-182 and miR-183C miRNAs regulate the inflammatory IFN in splenocytes via targeting Foxo1. The deletion of either miR-182 alone or the whole miR-183C cluster, however, had no marked effect on the composition of T and B cell subsets in the spleens of B6/lpr mice. There were similar percentages of CD4+, CD8+, CD19+, as well as Tregs, follicular helper T (TFH), germinal center B (GCB), and plasma cells in the miR-183C-/-B6/lpr and miR-182-/-B6/lpr mice and their respective littermate controls, miR-183Cfl/flB6/lpr and miR-182fl/flB6/lpr mice. Together, our data demonstrate a role of miR-183C in the regulation of anti-dsDNA autoantibody production in vivo in B6/lpr mice and the induction of IFN in in vitro activated splenocytes from B6/lpr mice.